WORD CHOICE, TONE, AND POINT OF VIEW IN THOMAS HARDY’S “THE CONVERGENCE OF THE TWAIN” - Suryo Tri Saksono (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2011)
Titanic was the most famous ocean liner in its time. It became more famous when it sank in April 1912. It inspires many authors to write literary works. One of them is Thomas Hardy who wrote “The Convergence of the Twain.” It portrays a tragedy of human pride in the sinking of the ship. Through analysis of word choice, tone, and point of view, some lessons are found: man can build and develop modern and sophisticated technology, but he will not be able to control his fate. The force of fate owned by the Almighty God is above everything.